An Interreligious Learning Program in Indonesia - JB. Heru Prakosa, SJ, (South Asian Journal of Religion and Philosophy (SAJRP), 2025)
Indonesia is a pluralist society in which mission can be understood by the act of witnessing to another faith. This enables one to practice one's faith in a more authentic way and to contribute to the common good. The inter-religious studies program at the University of Sanatan Dharma, Yogyakarta, Indonesia, does not depend solely on books and lectures but also involves actual experiences such as direct encounters, personal relationships, and direct participation. This approach to inter-religious studies has been inspired by Ignatian pedagogy, which consists of the following five steps: context, experience, reflection, action, and evaluation. The Ignatian approach provides a methodological framework for transmitting knowledge without disregarding the significance of vision, values, diverse ethical frameworks and interpersonal encounters. The Ignatian approach also facilitates a process in which one acquires deeper understanding of another cultural-religious tradition by the readiness to experience the beauty of another cultural-religious tradition and, subsequently, to appreciate one’s own tradition in a new way.